Fiscal Challenges for Australia: The Next Decade and Beyond. Issue 3 (19th August 2016) - Daley, John; Wood, Danielle
Abstract: In Australia, both the Commonwealth and state governments are running substantial budget deficits, and future challenges are likely to make these problems worse. This paper presents the key challenges facing these budgets. Falling terms of trade and lower nominal economic growth will drag on government revenues. Spending in health and infrastructure has grown faster than GDP. State government revenues are also affected by Commonwealth decisions to reduce grants to them. We also show how the government's short‐term and medium‐term projections rely on overly‐optimistic assumptions about organic revenue growth and spending restraint. As such, a drift back to surplus is unlikely and restoring budget sustainability will require Australian governments to make more politically difficult decisions. While containing spending is important, both the politics of budget repair and the sheer size of the budget gap means that they will not be able to bring their budgets to balance without also boosting revenues.